A novel and robust method for testing bimodality and characterizing porcine adipocytes of adipose tissue of 5 purebred lines of pig. (3rd April 2017) - Testroet, Eric D.; Sherman, Peter; Yoder, Chad; Testroet, Amber; Reynolds, Carmen; O'Neil, Mathew; Lei, Soi Meng; Beitz, Donald C.; Baas, Tom J.
ABSTRACT: Adipocyte sizes from adipose tissue of mature animals form a bimodal distribution, thus reporting mean cell size is misleading. The objectives of this study were to develop a robust method for testing bimodality of porcine adipocytes, describe the size distribution with an informative metric, and statistically test hypertrophy and appearance of new small adipocytes, possibly resulting from hyperplasia or lipid filling of previously divided fibroblastic cells. Ninety-three percent of adipose samples measured were bimodal ( P < 0.0001); therefore, we describe and propose a method of testing hyperplasia or lipid filling of previously divided fibroblastic cells based upon the probability of an adipocyte falling into 2 chosen competing "bins" as adiposity increases. We also conclude that increased adiposity is correlated positively with an adipocyte being found in the minor mode ( r = 0.46) and correlated negatively with an adipocyte being found in the major mode ( r = −0.22), providing evidence of either hyperplasia or lipid filling of previously divided fibroblastic cells. We additionally conclude that as adiposity increases, the mode of the major distribution of cells occurs at a larger diameter of adipocyte, indicating hypertrophy.